Syahādah Hilal Non Muslim dalam Hukum Islam dan Hukum Positif Indonesia - Zulfiah Zulfiah; Husni Idrus (Astroislamica: Journal of Islamic Astronomy, 2023)
Indonesia is a country that regulates religious life as reflected in the first principle of Pancasila. One of the religious lives regulated by the state is determining the start of the month of Ramadan and two holidays. The determination of the start of the months of Ramadhan, Shawwal and Zulhijjah is determined through an isbat session held by the Ministry of Religion of the Republic of Indonesia. The isbat session was held after the hilal rukyah team carried out hilal rukyah at the agreed rukyat locations from Sabang to Meurauke. Through a descriptive juridical approach, this research tries to find the position of non-Muslim crescent testimony in determining the beginning of the month in Indonesia. From existing data sources it can be concluded that the shahadah of non-Muslims can be accepted as an assistant, not as a determinant in determining the start of the Hijriah month.